Implementasi Program KKN Tematik Fun Study Home untuk Mendukung Motivasi Belajar Siswa Sekolah di Desa Rejuno (Lembaga Pengembangan Kinerja Dosen, 2026)
Learning activities outside school hours are needed to help students deepen their understanding of learning materials and increase their engagement in the learning process. The Fun Study Home program was implemented as a community service activity by university students participating in the Community Service Program (KKN) to provide interactive and enjoyable learning assistance for students at SDN Rejuno 1. This activity aimed to provide an alternative learning space through the implementation of various learning methods to support students' learning motivation, activeness, and social skills. The method used was descriptive qualitative through the stages of preparation, implementation, and evaluation, with data collection techniques consisting of observation, documentation, and activity evaluation results. The results showed that the Fun Study Home program was successfully implemented according to the planned objectives through discussion activities, question-and-answer sessions, exercises, digital quizzes, and educational games. This program has implications for creating a more active learning environment, increasing student participation, and becoming an alternative community service-based learning assistance program at the elementary school level.